Characterization Biofuel from Empty Fruit Bunch through Thermal Cracking - Daya Wulandari; Rusdianasari; Muhammad Yerizam (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2022)
Empty Fruit Bunches (EFB) are oil palm waste that has the potential as a source of bioenergy because it contains lignocellulose (cellulose, hemicellulose, and lignin) so that it can be converted into biofuel through thermal cracking, adsorption, and distillation processes. Thermal cracking is the decomposition of the chemical content of biomass by utilizing heat without a mixture of oxygen at a temperature of 200oC–600oC. This study aims to obtain the characteristics of the raw material of EFB in the form of proximate, ultimate, lignin, and biofuel produced. The research was conducted using a thermal cracking reactor designed to control the temperature at 300oC, 350oC, 400oC, and 450oC. The results showed that the raw material characteristics of EFB from proximate were 13.66% water content, 8.74% ash content, 58.66% volatile matter and 18.90% fixed carbon. This water content is relatively high. This is because the drying process on the material has not run perfectly. The ultimate result showed that the EFB had a C content of 54.45%, H content of 5.00%, and O content of 16.27%. The atomic ratio obtained from the ultimate analysis can indicate the amount of calorific value that can be used for certain fuels. The smaller the atomic ratio value contained, the more significant the calorific value contained in a particular fuel. Klason method was carried out to decrease the level of lignin through 4 stages; the lignin content without delignification was resulting into 24.87%, the addition of aquadest was resulting into18.71%, the addition of 5% HCl resulting into 15.34%, and 10% HCl resulting into 14.49%. Delignification of 10% HCl is the pretreatment process before the thermal cracking. The thermal cracking process forms steam; the steam is then condensed to obtain bio-oil. The formed bio-oil was kept to separate the oil from tar. In order to obtain good biofuel quality, adsorption is carried out with zeolite adsorbent, which has been activated with HCL. A comparison of the physical properties of bio-oil before and after adsorption shows a color difference from brownish black to the adsorbed bio-oil, which is distilled to separate the heavy and light fractions. The temperature of 450oC at thermal cracking is close to optimum; when the temperature is increased, the cracking process will be more straightforward and occur optimally. The biofuel produced in this study was tested for its characteristics such as, density (927-1086.68 Kg/m3), kinematic viscosity (1.17-1.43 mm2/s), and flash point (66.00-70, 23oC). The biofuel product produced is dominated by C5-C15 compounds (45.07%) according to the results of GC-MS analysis.